2013
DOI: 10.6061/clinics/2013(09)09
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular involvement in anterior myocardial infarction: a tissue Doppler-derived strain and strain rate study

Abstract: OBJECTIVE:Strain and strain rate imaging is currently the most popular echocardiographic technique that reveals subclinical myocardial damage. There are currently no available data on this imaging method with regard to assessing right ventricular involvement in anterior myocardial infarction. Therefore, we aimed to evaluate right ventricular regional functions using a derived strain and strain rate imaging tissue Doppler method in patients who were successfully treated for their first anterior myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the research by Sonmez et al, both systolic and diastolic functions were affected after anterior ST-elevation MI. They also found a significant increase in RV Tei index, as an important factor affecting prognosis, after anterior MI (15).…”
Section: Discussionmentioning
confidence: 95%
“…In the research by Sonmez et al, both systolic and diastolic functions were affected after anterior ST-elevation MI. They also found a significant increase in RV Tei index, as an important factor affecting prognosis, after anterior MI (15).…”
Section: Discussionmentioning
confidence: 95%
“…In a study, researchers utilized color-coded tissue Doppler imaging in patients with ASTEMI and demonstrated a decline in RV systolic function [ 26 ]. They, however, failed to define the time of echocardiography after ASTEMI, and they used an echocardiography modality that was not only dependent on the ultrasound beam angle but also associated with low spatial resolution, high noise, and interobserver variability [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…S/SR imaging is currently a very important echocardiographic modality for revealing subclinical myocardial damage. 51 In another study, Marmor et al 52 showed that in patients with anterior MI there was persistent regional and global impairment of LV function but only transient impairment of the RV, whereas inferior infarction was associated with severe, persistent regional and global impairment of the RV. In fact, in 22 patients who had anterior MI, the global RV ejection fraction was decreased reflecting a uniform depression of function without localized abnormalities and returned to normal by the tenth day.…”
Section: Human Modelsmentioning
confidence: 98%
“…However, this is not supported by anatomical and functional considerations. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In addition, RV involvement is an independent predictor of major cardiac adverse events. 43 In clinical practice low importance has been deserved to the RV during initial evaluation of the patients with acute settings of the anterior STEMI.…”
Section: Which Is the Best Technique?mentioning
confidence: 99%
See 1 more Smart Citation